Discriminant = √[(2√6)^2 - 4 * 3 * 2] = 0
=> 3x^2 + 2√6x + 2 is a perfect square and is
= (√3x + √2)^2
An expression cannot be solved. It can be simplified. If you are meaning to solve the equation
3x^2 + 2√6x + 2 =, then its is
(√3x + √2)^2 = 0
=> x = - √(2/3).
[root3x}^2+ 2 X root3x X root2 + [root 2]^2
[Root3x + root 2] ^2
I hope you know your lack of brackets has made this thing unreadable. Does the square root only cover the 6? Does it go all the way to the 2?
In given form , question has no mathematical meaning.
Could there be an = sign somewhere?
Could there be a zero somewhere?
(x√3 + √2)2
then x = -√2/√3 double root
you put brackets to break down the sum
because you don't know what x2 is you just have to leave it at that unless in gives you the number for what x2 stands for
i don't know if this is right i am just guessing lol
well .. by looking at it , it tells ..
3x2 = (√3x)2 = a2
2 = (√2)2 = b2
and 2√6 = 2.√3.√2 = 2ab
=> 3x2+2√6x+2 = (√3x + √2)2
==> x= -√(2/3)
NOTE : i did these kinds of sums so i could figure out that it was a whole square by looking at the nos.
bt .. i would suggest you to find out the discriminant (b2-4ac) before solving .. which comes out to be 0 .. indicating it has equal roots .. which means it is a perfect square ! :)